Non-Performing Finance dalam Memoderasi Pengaruh Dana Pihak Ketiga, Capital Adequacy Ratio, dan Financing to Deposit Ratio terhadap Return on Assets Bank Umum Syariah Periode 2016-2021 - Amrina Rosada, Eka; Aulia, Fira (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
The purpose of this study was to analyze the influence of Non-Performing Finance (NPF) in moderating the relationship between Third Party Funds, Capital Adequacy Ratio (CAR), and Financing to Deposit Ratio (FDR) to Return on Assets (ROA) at Commercial Banks Sharia in Indonesia for the 2016-2021 period. This research is a type of quantitative research with a correlational approach. By using purposive sampling technique, 8 Commercial Banks Sharia were obtained as research samples. The data analysis technique used to answer the hypothesis in this study uses Moderated Regression Analysis (MRA). The results of the study concluded that partially Third-Party Funds had no effect on ROA, while the CAR and FDR variables partially had an effect on ROA at Islamic Commercial Banks for the 2016-2021 period. Furthermore, when there is the addition of NPF as a moderating variable, the research findings state that NPF is not able to moderate the effect of Third-Party Funds on ROA. Meanwhile, on the other hand, NPF is able to moderate the influence of CAR and FDR on ROA of Islamic Commercial Banks for the 2016-2021 period.